Pengaruh Mailing Groups Sebagai Media Diskusi Dalam Motivasi Belajar Mahasiswa - Aini, Qurotul; Rahardja, Untung; Supriyati, Ruli; Khoirunisa, Alfiah (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
In the current era of globalization, technology management has touched every part of human life. The combination of these two factors will become a new innovation in the management of education. At Raharja College, the entire academic community has a facility in the form of an official e-mail, Rinfo, which functions as a communication medium. Therefore, it is necessary to optimize the use of RinfoApps which is used as a discussion medium for online learning. Mailing Groups is one of the Google System features that can be used as a formal media for the online learning discussion management process. By creating a forum called the class mailing list on Mailing Groups, students and lecturers can discuss anytime, students can share about learning material, and lecturers can also monitor the activeness of student discussions, this certainly has an important influence on learning motivation college student. Supported by 2 (two) research methods, namely library research and observation methods. The final results of the research that has been achieved are the formation of a discussion media that is easily accessible anywhere and anytime so that the discussion process between students and lecturers becomes more effective and efficient.